The Horror of Police - Linnemann, Travis (University of Minnesota Press, 2022)
Cover Page -- Title Page -- Copyright Page -- Contents -- Introduction: Police Story, Horror Story -- Chapter 1: Bad Cops and True Detectives -- Chapter 2: The Police at the End of the World, or The Political Theology of the Thin Blue Line -- Chapter 3: RoboCop, or Modern Prometheus -- Chapter 4: Monsters Are Real -- Chapter 5: The Unthinkable World -- Acknowledgments -- Notes -- Index -- About the Author.